Attitude and participation of men regarding prenatal care, Childbirth, and postpartum care in Kashan City, Iran - Fatemeh Waseghi; Saeideh Nasiri; SeyyedAlireza Moravveji; Zahra Karimian (Wolters Kluwer Medknow Publications, 2021)
Background: Men's involvement in perinatal care has benefits including reduced preterm childbirth, and better development of children. This study was conducted with the aim to determine the attitude and participation of men in prenatal, childbirth, and postpartum care. Materials and Methods: This cross-sectional study was performed on 280 men in industrial units in Kashan city, Iran (November 2014-March 2015). The participants were selected using cluster sampling method. They completed a researcher-made three-part questionnaire. The data were analyzed using independent-samples t test and analysis of variance (ANOVA). Results: The mean (SD) score of men's attitude and practice regarding perinatal care were 40.12 (5.00) and 61.65 (6.87), respectively. A significant difference was observed between the practice of men with different education levels (F2,75 = 3.63, p = 0.001). Conclusions: The participation of men in perinatal care was low. It is recommended that healthcare providers make visits in the presence of husbands and simultaneously provide training for the couples during the perinatal period.